Konstruksi Makna Kepemimpinan Perempuan dalam Birokrasi Pemerintahan di Indonesia - Reny Henriyani; Bunga Shafa Azizah; Mahbub Ubaedi Alwi; Ganjar Ndaru Aji; Aldi Hardianto (Jayapangus Press, 2026)
Women’s leadership in government bureaucracy is increasingly recognized for contributing to more inclusive and responsive public policies. However, in Indonesia, women’s representation in strategic leadership positions remains limited, indicating persistent structural and cultural barriers. Previous studies have largely focused on structural aspects and numerical representation, while limited attention has been paid to how women leaders construct meaning and legitimacy through communication practices. This study explores how female Indonesian civil servants construct, negotiate, and interpret their leadership roles, particularly through communication practices related to public policy formulation and implementation. Employing a qualitative approach with an interpretative phenomenological design, data were collected through in-depth interviews with five mid-level women leaders in the Indonesian civil service involved in public policy processes. Data were analyzed thematically using Berger and Luckmann's social construction framework enriched by a leadership-as-communication perspective. The findings indicate that the meaning of women's leadership is dialectically constructed through three main processes: internalization of leadership values through social and professional experiences; objectivation through negotiation with organizational structures, bureaucratic norms, and social expectations; and externalization through adaptive communication practices that contribute to shaping more humane and responsive public policies for vulnerable groups. Academically, this study argues that women's leadership can be understood as a communicative practice that not only reflects bureaucratic structures but also dialectically reconstructs public policy orientations.